The Influence of Compensation on the Quality of Work Life in A Company In Southern Sonora - Claudia Robles Camacho; Campas, Celia Yaneth Quiroz; Lizeth Armenta Zazueta; Carlos Jesús Hinojoza Rodríguez; Alberto Galván Corral; Cecilia Aurora Murillo Félix (International Journal of Medical Toxicology and Legal Medicine, 2024)
The most valuable resource that a company or organization has is undoubtedly human capital, which is why companies must create strategies that motivate workers, such as having a compensation program that helps in the quality of work life and thus manage to keep their staff. This research work was carried out in a company in southern Sonora, with the participation of both operational and administrative personnel. The objective of this work is to evaluate the influence that compensation has on the quality of work life of the workers of a company in southern Sonora, through the application of an instrument and a focus group, this to generate a proposal for improvement of its workers. The methodology applied is mixed, quantitative and qualitative, the dimensions of quality of life, organizational management and organizational performance were evaluated. The answers were given through a Likert scale, with the results of: quality of life with 89.0%, organizational management with 90.8% and organizational performance with 89.2%, with the dimension of organizational management being the best evaluated. A focus group was also held which made us aware that the influence of compensations is favorable, since it helps them in their family economy. Based on the results, it is concluded that the influence of compensation on the quality of work life in the workers of a company in southern Sonora is positive, since it greatly helps in the quality of work life of the workers.